RET somatic mutations are underrecognized in Hirschsprung disease. (July 2018) - Jiang, Qian; Liu, Fang; Miao, Chunyue; Li, Qi; Zhang, Zhen; Xiao, Ping; Su, Lin; Yu, Kaihui; Chen, Xiaoli; Zhang, Feng; Chakravarti, Aravinda; Li, Long
Abstract Purpose We aimed to determine the frequency ofRET mosaicism in Hirschsprung disease (HSCR), test whether it has been underestimated, and to assess its contribution to HSCR risk. Methods Targeted exome sequencing (n  = 83) andRET single-gene screening (n  = 69) were performed. Amplicon-based deep sequencing was applied on multiple tissue samples. TA cloning and sequencing were conducted for validation. Results We identified eight de novo mutations in 152 patients (5.2%), of which six were pathogenic mosaic mutations. Two of these patients were somatic mosaics, with mutations detected in blood, colon, and saliva (mutant allele frequency: 35–44%). In addition, germ-line mosaicism was identified in four clinically unaffected subjects, each with an affected child, in multiple tissues (mutant allele frequency: 1–28%). Conclusion Somatic mutations of theRET gene are underrecognized in HSCR. Molecular investigation of the parents of patients with seemingly sporadic mutations is essential to determine recurrence risk in these families.